Respuesta :

Answer:he age of the person who entered the room = 27 years

Step-by-step explanation:

Step 1

Mean  Age  = total of the ages of observation / numbers of people with the ages

Step 2

Let the sixth person's age be represented as x

such that the mean ages of the 6 people inside the room be given as

Mean =Total ages  of 6 people / 6  

20 = Total ages  of 6 people / 6  

(16+25+23+12+17+ x) / 6 = 20

93+ x / 6 = 20

93+ x= 6 x 20

93+ x= 120

x= 120 - 93

x=27

the age of the person who entered the room = 27 years

 

ACCESS MORE